The future of the global church : history, trends and possibilities - Johnstone, Patrick J. St. G. (Colorado Springs, CO : Biblica ; [Bucks, England] : WEC International, 2011)
"... weaves together the strands of history, demographics and religion to present a breath-taking, full-color graphical and textual overview of the past, present and possible future of the Church around the world. ... a thought-provoking glimpse into likely scenarios humankind may face in the next 40 years. ... highlights the impact of evangelical Christianity over the past two centures, as well as the astonishing growth of Evangelicalism over the past half century. ... a special emphasis on the world's 12,000 people groups--especially those that have had least exposure to the Gospel. ... Johnstone homes in on the role of the local church in tackling the unfinished task of world evangelization, especially that of reaching the world's least evangelized peoples with the Gospel." -- back cover.
Demography: nine global challenges -- History: 20 centuries AD -- Religion: the major streams -- Christianity: six megablocs -- Christianity: renewal growth -- Christianity: the evangelical explosion -- The unevangelized -- Christian missions and the future -- Conclusion: an evangelized world?
Maps on end papers.
Includes bibliographical references (p. 240)
Keywords: Church and the world; Missions -- Theory; Missions -- History; Christianity; Missions -- Forecasting; Christianity -- Forecasting; Evangelicalism; Ethnic groups -- Missions; Mission of the church